Natural values as a factor in the location of residential investments - Arnold Bernaciak; Natalia Strzelecka (Economic and Environmental Studies (E&ES), 2014)
The natural environment is one of the factors of development activities location. The quality and availability of natural values influences bid prices of flats. The availability of ecosystems of special qualities such as rarity and uniqueness is not a desirable feature for potential buyers. This is due to conservation restrictions, and thus the limited possibilities to use the land for recreational purposes. The most desirable category are the green areas located within the urban structure, which provide the opportunity to combine a sense of communion with nature and relatively unrestricted use of the benefits offered by ecosystems.
Keywords: 330; natural values; housing investments; Poznan agglomeration